PENGARUH KEAMANAN, KEPERCAYAAN DAN KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE FJB HP IPHONE DI KOTA BATAM - Laoli, Liberniwati; Wage, Sunarto (JURSIMA, 2022)
This study investigates the impact of security, trust, and ease of use factors on purchasing decisions in the FJB HP iPhone marketplace in Batam City. The research uses a quantitative approach with a survey method, focusing on active marketplace users who have purchased an iPhone in the last three years and live in Batam City. The study uses a questionnaire with a 5 Likert scale for data analysis using SPSS version 26 program. The results show that security factors have a positive influence on purchasing decisions, but the effect is relatively small compared to other variables. Trust has a positive and significant influence on purchasing decisions, with a regression coefficient of 0.134 and a p-value of 0.045. Ease of use is the most significant factor in influencing purchasing decisions, with a highest regression coefficient of 0.930 and p-value <0.001. The study emphasizes the importance of optimal user experience in e-commerce platforms. The combination of security, trust, and convenience factors collectively has a significant influence on purchasing decisions, with a high predictive power and 84.2% of variation explained by the interaction of the three independent variables.